Properties of concrete incorporating eggshell as partial cement replacement with tire crumb as sand replacement - Chong, Beng Wei (2021)
Rapid urbanization has led to a sharp increase of construction and hence cement usage, a material which contributes greatly to greenhouse gas emission due to high energy consumption. The cement industry is among the largest contributors of greenhouse gas. About 7% of global CO2 emission comes from the industry, with 900 kg CO2 emitted to the atmosphere for producing one ton of cement. Solid waste management is one the leading problems in Malaysia. Rapid development and population growth have prompted researches to improve the recycling and reusing of waste material for sustainable development. Chicken eggshell is discarded in Malaysia as municipal waste, while waste tire is a waste that is difficult to handle and often ends up in the landfill. This paper presents the properties of high performance concrete with eggshell powder and tire rubber crumb as partial replacement of cement and sand. The eggshell was grinded to size passing 150µm sieve while waste tire rubber of 30mesh or 600µm was purchased for the study. Grade 55 high-performance concrete was prepared with up to 15% eggshell as cement replacement and up to 15% tire rubber crumb as sand replacement at an interval of 5% for both materials. The physical properties of concrete specimens were evaluated with various tests such as slump cone test and porosity test. Non-destructive tests, namely rebound hammer and ultrasonic pulse velocity are then conducted on the specimens. Mechanical tests are then conducted to determine the compressive strength, flexural strength and modulus of elasticity of concrete specimens. Design of experiment was used to analyse all collected data and determine the optimum percentage of replacement. Mixed regression and Response Surface Methodology were employed to produce mathematical models of concrete workability and compressive strength. The result shows that both eggshell and tire rubber reduces workability of concrete. However, the optimum specimen with 5% eggshell and tire rubber retained medium workability. Porosity of concrete decreases with eggshell replacement and the optimum specimen has a porosity of 2.71%. Based on non-destructive tests, the rebound number of optimum specimen is 29.50 which indicates satisfactory surface hardness. Meanwhile, both control and optimum concrete specimens achieve high-quality status with UPV value above 4km/s. For mechanical properties, optimum concrete specimen observes a 13.46% increase in compressive strength to achieve 28-days compressive strength of 55.37 MPa. Flexural strength of the optimum specimen recorded 11.245 MPa which is 11.969% higher than the control. In addition, split tensile strength of optimum specimen increases by 8.528% to 35.78MPa. Microstructure analysis of concrete reveals that replacement of cement with eggshell causes a greater hydration rate, denser internal packing, and less internal voids. Mathematical modelling using non-destructive test and replacement proportion shows that eggshell powder replacement has a curvilinear relation with concrete mechanical performance. The models have coefficient of determination above 0.90 while the predicted value from the model has deviation within ±10% from the experimental value. Both regression and RSM model could predict the behaviour of concrete, but Response Surface Methodology model has lower deviation and better accuracy. Hence, eggshell powder and tire rubber concrete is concluded as a feasible option in concrete production for the conservation of natural resources and raw materials